Frequency and Stratification of Epileptogenic Lesions in Elderly With New Onset Seizures - Arabi, Maher; Dirani, Maya; Hourani, Roula; Nasreddine, Wassim; Wazne, Jaafar; Atweh, Samir; Samara, Heba; Shatila, Abdel Rahman; Beydoun, Ahmad (Frontiers in Neurology, 2018)
Objective: To prospectively evaluate the frequency of epileptogenic lesions in a consecutive cohort of elderly patients presenting with new onset unprovoked seizures, and who underwent a complete evaluation including dedicated epilepsy protocol MRI. Methods and materials: We included all consecutive patients 60 years or older who participated in a prospective study on new onset epilepsy. The work-up included the acquisition of a dedicated epilepsy protocol MRI and a three hours video/EEG recording. We evaluated the frequency and types of epileptogenic lesions in the whole cohort and stratified those variables by age, gender, types and number of seizures at presentation. We also correlated the EEG findings with the clinical characteristics and neuroimaging results. Results: Of the 101 patients enrolled in the study and who underwent an epilepsy protocol MRI, an epileptogenic lesion was identified in 67%. The most common etiologies were vascular events, followed by tumoral causes and traumatic brain injuries. Epileptogenic lesions were more likely to be identified in patients who presented with only focal aware and impaired awareness seizures. In addition, patients with tumoral epilepsy were significantly more likely to only experience those seizure types compared to patients with other pathological substrates. Interictal/ictal discharges were detected in the EEG of 21% of patients. Epileptiform discharges were significantly more frequent in patients with an epileptogenic lesion on brain MRI, especially in those with a brain tumor. Conclusions: Our results stress the importance of obtaining a dedicated epilepsy protocol MRI in elderly patients with new onset seizures. An epileptogenic lesion will be identified in approximately two thirds of patients with important implications regarding initiation of treatment. In addition, the data underscore the value of distinguishing the types of seizures experienced at presentation as this will apprise the treating physician on the likelihood of identifying an epileptogenic lesion and on the probable etiologies.